Perancangan Interior Daycare Center Sebagai 2nd Home Di Surabaya - Kwong, Juwita Priscella (Intra, 2015)
The busyness of career women who serve as housewives and also work for a living makes them lack the time to take care of their babies. Whereas the early education is the most important, when the kids are in